THE USE OF ENGLISH MEDIUM INSTRUCTION ON EFL STUDENTS AT TERTIARY EDUCATION LEVEL - Nirma Paris; Pratiwi Samad; Faridah Abdul Rauf (Institut Agama Islam Negeri Parepare, 2022)
English medium instruction has been used in many education levels. Although L2 learners study English since primary education, some of them still cannot communicate and write well in English. It is probably caused by lack of self-esteem, motivation, comprehensible input, and interaction. The present study aimed to investigate the use of English medium instruction on EFL students at tertiary education level. This study employed a quantitative method. The participants of this study were 45 undergraduate students at Khon Kaen University, Thailand. A survey questionnaire regarding the use of English medium instruction with a five point likert scale was assigned to the participants in order to obtain the data. The result of this study revealed that there are some subjects that use English as medium of instruction. Furthermore, the students stated that they got exposure in English in several ways such as read textbook, watch YouTube, and write power point in English. The results also showed that the students’ English ability significantly improve regarding the use of English as medium of instruction